Cat Scratch Disease – The Inconspicuous Cause of Cervical Lymphadenopathy - Prasanth Panicker; P. Manoj Kumar; Feby Francis; Ashford Lidiya George (Journal of Pharmacy and Bioallied Sciences, 2025)
Bacterial cat scratch disease (CSD), also called cat scratch fever or subacute regional lymphadenitis, affects lymph nodes draining from the implantation site. Bartonella henselae causes most CSD and could be regarded as a cause of concern for acute lymphadenopathy in individuals of all ages. CSD frequently resembles cervical lymphadenopathy or submandibular gland disorders, making diagnosis difficult. This study describes a 12-year-old girl who contracted cat scratch disease with swelling of submandibular lymph nodes following intimate contact with a pet cat.